Health of Russian medical university students: problems and solutions - P. V. Glybochko; I. E. Esaulenko; V. I. Popov; T. N. Petrova (Сеченовский вестник)
The article presents data on the state of health of modern youth and organizational forms of rendering medical and preventive assistance for medical university students in Russia. The article provides an overview of student health status and health care activities, the sources of information on healthy lifestyles. The article discusses subjective factors of health and healthy lifestyle: diet, student and sports leisure time activities, bad habits. The article summarizes the long work results on both general theoretical-methodological approaches and practical mechanisms of health care activities organization and management in university students; the basic shortcomings of medical care for this cohort. The article puts forward options for disease prevention and rehabilitation optimization in university students. The problem requires a new approach to guarantee the quality health care for university students, innovative forms of organization, establishment of uniform model of student health management.